PERBANDINGAN DIMENSI VERTIKAL WAJAH PADA MALOKLUSI ANGLE KELAS II DIVISI 1 DENGAN PENCABUTAN GIGI POSTERIOR BERBEDA SETELAH PERAWATAN TEKNIK BEGG - , Fransiska Windayanti Inan, drg. Sri Suparwitri SU., Sp.Ort (K) ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The aim of the study was to evaluate and compare the changes of facial vertical dimension in Angle class II division 1 malocclusion with different mandibular posterior teeth extraction pattern after Begg technique treatment. There were three lateral cephalometric measurements of facial vertical dimension, namely Anterior Facial Height, Posterior Facial Height and Mandibular Plane angle. The study was done at 32 subjects with criteria : Angle class II division 1 malocclusion, class I or II skeletal, aged 18-30 years, no extraoral appliances were used. There were three groups with different posterior teeth extraction pattern. The first group consisted of 15 subjects with both of maxillary first premolar teeth extraction and both of mandibular first premolar teeth extraction. The second group consisted of 7 subjects with both of maxillary first premolar teeth extraction and both of mandibular second premolar teeth extraction. The third group consisted of 10 subjects with both of maxillary first premolar teeth extraction and both of mandibular first molar teeth extraction. The changes of facial vertical dimension between the pre and post treatments were analized using paired t test, meanwhile the differences of facial vertical dimension between the three groups were analized using Anova. The result of the study showed Anterior Facial Height, Posterior Facial Height and Mandibular Plane angle increased significantly (p<0.05) in the three groups. No significant (p>0.05) differences in increasing of Anterior Facial Height, Posterior Facial Height and Mandibular Plane angle between the three groups.